Analysis of Factors Influencing Cardiovascular Events and Mortality in Patients on Dialysis after Parathyroidectomy - Yang, Taohong; Xue, Yang; Ren, Jianping; Li, XinYu; Xu, Wenting; Nie, Guangyang; Wang, Deguang; Wang, Xuerong (Current Pharmaceutical Design, 2025)
BackgroundRenal secondary hyperparathyroidism (SHPT) represents a prevalent complication among dialysis patients, significantly impacting long-term prognosis. Parathyroidectomy (PTX) serves as a clinically effective therapeutic option for patients diagnosed with refractory secondary hyperparathyroidism.ObjectiveThis study aims to assess the impact of PTX on cardiovascular events (CVEs) and all-cause mortality in dialysis patients, as well as to analyze the incidence and potential determinants of postoperative cardiovascular events and all-cause mortality.MethodsWe collected data on 710 patients with renal secondary hyperparathyroidism who were treated with PTX between February 2011 and April 2019. A total of 633 patients who underwent PTX were finally included and matched with 462 patients who did not undergo PTX on a 1:1 basis according to age and follow-up duration. Ultimately, 179 pairs were successfully matched to investigate the differences in all-cause mortality and CVEs. The Logistic/Cox regression analyses were employed to identify independent factors associated with adverse CVEs and all-cause mortality among patients receiving PTX. Nomogram prediction models were constructed based on independent influencing factors.ResultsAmong 633 patients who underwent PTX, 117 (18.5%) died and 192 (30.3%) experienced CVEs during median 5-year follow-up. No significant differences in cardiovascular/death events were observed between matched groups. In patients who underwent PTX, the logistic regression analysis revealed that age and history of diabetes mellitus were independent risk factors for CVEs. The pre-operative use of cinacalcet and/or calcitriol was associated with a reduced risk of CVEs. With respect to preoperative and postoperative calcium levels, the highest tertile was identified as a risk factor when compared with the lowest tertile. Cox regression showed age, diabetes history, and highest preoperative phosphorus tertile negatively correlated with survival, while albumin (ALB) was positively correlated. The predictive nomogram model had an area under the receiver operating characteristic (ROC) curve of 0.649 for CVE prediction. The areas under the ROC curve for predicting 3-, 5-, and 10-year mortality prediction were 0.865, 0.865, and 0.953, respectively.ConclusionPTX does not reduce the incidence of cardiovascular events and mortality in patients on maintenance dialysis. In patients who underwent PTX, older age, a history of diabetes mellitus, and higher preoperative calcium/postoperative calcium levels were independent risk factors for adverse CVEs; preoperative use of cinacalcet and/or calcitriol was a protective risk for CVEs. Older age, a history of diabetes mellitus, lower ALB levels, and hyperphosphatemia were independent risk factors for all-cause mortality following PTX. These predictive models may assist in clinical decision-making to some extent.
Keywords: all-cause mortality